PENGEMBANGAN LKPD ELEKTRONIK BERBASIS SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) PADA MATERI SISTEM EKSKRESI UNTUK MELATIHKAN KETERAMPILAN LITERASI DIGITAL PESERTA DIDIK KELAS XI SMA - Vania Putri, Nabilah; Yuliani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology requires students to possess adequate digital literacy skills to effectively search, evaluate, and process information. This study aimed to describe the practicality and effectiveness of an electronic student worksheet (E-LKPD) based on the Science, Environment, Technology, and Society (SETS) approach on the Human Excretory System topic to enhance the digital literacy of eleventh-grade senior high school students. This study employed the 4D development model (Define, Design, Develop, and Disseminate) and was conducted up to the Develop stage. A limited trial was carried out involving 30 eleventh grade students of MAN Kota Surabaya. The practicality of the E-LKPD was assessed through learning implementation observations and student response questionnaires, while its effectiveness was evaluated based on group worksheet performance and the improvement of students' digital literacy skills measured using the N-Gain score. The results showed that the E-LKPD demonstrated a very high level of practicality, with a learning implementation score of 100% and a student response rate of 99.84%. The E-LKPD was also proven effective, as indicated by an average group performance score of 95, with all groups achieving scores above the minimum mastery criterion (≥75), and an average N-Gain score of 0.77, which falls into the high category. Therefore, the SETS-based E-LKPD is considered practical and effective as a biology learning medium to enhance the digital literacy skills of eleventh grade senior high school students.